bamdit: An R Package for Bayesian Meta-Analysis of Diagnostic Test Data - Verde, Pablo Emilio (Journal of Statistical Software, 2018)
In this paper we present the R package bamdit. The name of the package stands for "Bayesian meta-analysis of diagnostic test data". bamdit was developed with the aim of simplifying the use of models in meta-analysis, that up to now have demanded great statistical expertise in Bayesian meta-analysis. The package implements a series of innovative statistical techniques including: the Bayesian summary receiver operating characteristic curve, the use of prior distributions that avoid boundary estimation problems of variances and correlations of random effects, analysis of conflict of evidence and robust estimation of model parameters. In addition, the package comes with several published examples of meta-analysis that can be used for illustration or further research in this area.